PENGARUH AKTIVITAS INTERNASIONAL, TIPE INDUSTRI DAN GROWTH OPPORTUNITY TERHADAP ELEMEN INTEGRATED REPORTING (Studi Empiris pada perusahaan non-keuangan yang terdaftar di BEI tahun 2015) - Rini Purnama Sari; Novita Indrawati; Edfan Darlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this research is to explore the effect of international activity, profil of industry, and growth opportunity on elemen of integrated reporting. The population in this research is 445 industry non-financial registered in BEI 2015 . In this research the sample used is the 85 industry were selected using random sampling method. This research used secondary data.. Technical analysis for test hypothesis that used in this research are multiple linear regression. The result of this research showed that International Activity significant effect, Profil of Industry significant effect ,Growth Opportunity have not significant effect .Keyword : International Activity, Profil of Industry, Growth Opportunity, Elemen of Integrated Reporting